2019
DOI: 10.1093/jmcb/mjz023
|View full text |Cite
|
Sign up to set email alerts
|

Discovering small molecules as Wnt inhibitors that promote heart regeneration and injury repair

Abstract: There are intense interests in discovering proregenerative medicine leads that can promote cardiac differentiation and regeneration, as well as repair damaged heart tissues. We have combined zebrafish embryo-based screens with cardiomyogenesis assays to discover selective small molecules that modulate heart development and regeneration with minimal adverse effects. Two related compounds with novel structures, named as Cardiomogen 1 and 2 (CDMG1 and CDMG2), were identified for their capacity to promote myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…A similar observation of cells expressing CM markers at the epicardial side was reported by treating female rats with ICG-001, a compound blocking the binding of b-catenin to the transcription complex (Sasaki et al, 2013). Recently, targeting WNT/b-catenin at the level of the transcription complex was also demonstrated to increase the newly formed CMs and reduce scarring in the zebrafish model of apical amputation (Xie et al, 2019). Taken together, the majority of studies now shows that targeting WNT/b-catenin at the level of the transcription complex by either a genetic or a pharmacological intervention induces a proliferative response in cells showing expression of CM markers located at the epicardial and endocardial borders of the infarct.…”
Section: Wnt Signalingsupporting
confidence: 69%
“…A similar observation of cells expressing CM markers at the epicardial side was reported by treating female rats with ICG-001, a compound blocking the binding of b-catenin to the transcription complex (Sasaki et al, 2013). Recently, targeting WNT/b-catenin at the level of the transcription complex was also demonstrated to increase the newly formed CMs and reduce scarring in the zebrafish model of apical amputation (Xie et al, 2019). Taken together, the majority of studies now shows that targeting WNT/b-catenin at the level of the transcription complex by either a genetic or a pharmacological intervention induces a proliferative response in cells showing expression of CM markers located at the epicardial and endocardial borders of the infarct.…”
Section: Wnt Signalingsupporting
confidence: 69%
“…The compound Cardiomogen 1 (CDMG1) was suggested by preliminary work to inhibit β-catenin and to negatively affect TCF/LEF-mediated transcription. Thus, CDMG1 was tested in a mouse permanent LAD ligation model and it exhibited a strong inhibitory effect on the scar length, indicating a smaller infarct [ 63 ]. In the same direction, Matteucci et al applied the small molecule WNT inhibitor SEN195 in rats overexpressing a β-catenin responsive TCF/LEF reporter via AAV9 gene therapy.…”
Section: Effect Of Interventions In Wnt Signaling On Infarct Sizementioning
confidence: 99%
“…Administration of the small molecule β-catenin/TCF inhibitor SEN195 exhibited a strong ~1.5-fold increase in EF and important reductions in LV volumes in both systole and diastole, in a mouse MI model [ 15 ]. Notably, similar beneficial effects in EF and FS and LVIDD were conferred by CDMG1 i/p injections when administered for 27 days in mice following MI [ 63 ]. It is clear that the conclusions from the above studies point to an attenuating effect of WNT/β-catenin signaling inhibition on cardiac dysfunction and thus, a beneficial effect in attenuating LV remodeling.…”
Section: Effects Of Interventions In Wnt Signaling On Cardiac Funcmentioning
confidence: 99%
“…For instances, proliferative CMs in zebrafish are mononuclear and diploid, whereas most adult human CMs become polyploidy that restrains CM proliferation (Xin et al, 2013;Tzahor and Poss, 2017). Although CM renewal is extremely low in uninjured mammalian hearts, a small number of proliferative CMs can be detectable in the injury border zone of murine hearts after myocardial infarction (Malliaras et al, 2013;Xiang et al, 2016;Xie et al, 2020). We believe that specific factors and mechanisms obtained from zebrafish regeneration study should be confirmed in mammal system such as mouse before exploring potential therapeutics in humans.…”
Section: Discussionmentioning
confidence: 99%